A Study on V2G Based Frequency Control in Power Grid with Renewable Energy. Issue 4 (2019) - Kumano, Teruhisa; Horita, Masaki; Shinada, Masahiro; Li, Xiaoyang
Abstract: Although renewable energy based power generation is the most promising and sophisticated solution to the future society owing to its small amount of emission of the greenhouse effect gas, it has a great disadvantage of varied output. For instance, the large amount of existing PVs already gives a serious destabilizing effect on the western Japanese power systems. It is of great concern how future power grid can be operated securely when great amount of renewable based power plants are installed. One of the promising countermeasures against this problem is the utilization of battery energy storage, where its highly costly impact, which comes from the necessary battery storage installation, can be mitigated if the electric vehicles are used for this stabilizing control. This paper proposes a new method for the above stated technical challenge. So called Euler equation in the field of calculus of variation is solved numerically satisfying equality and inequality constraints based on the assumed scenario of usable electric vehicles, providing the most desirable charge/ discharge plan. Numerical study is done to confirm the fundamental feasibility of the proposed method. This method is a great candidate to be applied to general cases of many realistic constraints.